1995
DOI: 10.1016/0014-5793(95)00369-k
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibition reduces the plateau phase of the calcium increase in response to progesterone in human sperm

Abstract: Progesterone (P) has previously been shown to induce a rapid increase in [Ca2+]i as well as tyrosine pbosphorylation of proteins in human spermatozoa. Both these effects are essential for induction of the acrosome reaction by P. We investigated a possible relationship between the P-induced calcium increase and tyrosine kinase activation, by evaluating the effect of the tyrosine kinase inhibitor genistein on these two effects. We found that preincubation with genistein abolished P-induced tyrosine phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 24 publications
8
37
0
1
Order By: Relevance
“…Progesterone induces the tyrosine phosphorylation of 94 kDa (Tesarik et al 1993) and 97 kDa (Bonaccorsi et al 1995) human sperm proteins. Although similar in molecular weight, it is not known whether these proteins correspond to either human pro-AKAP82 or AKAP82 (actually pro-AKAP4 and AKAP4).…”
Section: Pro-akap4 Mediates Dmbt1 Action On Porcine Spermmentioning
confidence: 99%
“…Progesterone induces the tyrosine phosphorylation of 94 kDa (Tesarik et al 1993) and 97 kDa (Bonaccorsi et al 1995) human sperm proteins. Although similar in molecular weight, it is not known whether these proteins correspond to either human pro-AKAP82 or AKAP82 (actually pro-AKAP4 and AKAP4).…”
Section: Pro-akap4 Mediates Dmbt1 Action On Porcine Spermmentioning
confidence: 99%
“…A similar situation applies for the phospholipase C/inositol3phosphate/diacylglycerol/protein kinase (PLC/IP3/DAG/PKC) pathway: although the enhancing effect of P on inositol trisphophate (Thomas and Meizel, 1989) and diacylglycerol (O'Toole et al, 1996a) synthesis has been reported, blockers of phospholipase C do not appear to affect P-stimulated Ca 2+ fluxes (Harper et al, 2004), and whether the pathway is involved in the induction of AR remains controversial (O'Toole et al, 1996b;Bonaccorsi et al, 1998). P at micromolar concentrations has been also shown to promote tyrosine phosphorylation of sperm proteins (Tesarik et al, 1993;Luconi et al, 1995) and this pathway is involved in AR and Ca 2+ influx in response to the steroid (Martinez et al, 1999;Bonaccorsi et al, 1995). However, as for cAMP generation, tyrosine phosphorylation increase in response to P is small Kirkman-Brown et al, 2002) and its influence on Ca 2+ transients and AR is discussed (Kirkman-Brown et al, 2002).…”
Section: P-induced Acrosome Reactionmentioning
confidence: 99%
“…In line with these observations, there is evidence demonstrating that PTH activates c-Src in osteoblastic cells through changes in tyrosine phosphorylation (Izbicka et al 1994 (Tsunoda et al 1996). Furthermore, Src family kinases have been implicated in the control of receptor-operated Ca 2+ influx in various cell types (Niklinska et al 1992, Lee et al 1993, Bonaccorsi et al 1995, Fleming et al 1995. Of interest, in colonic smooth muscle cells, the biphasic activation of ceramideinduced Src kinase activity was shown to be dependent on extracellular Ca 2+ in the second, sustained phase of activation (Ibitayo et al 1998).…”
Section: Discussionmentioning
confidence: 91%